2021
DOI: 10.1186/s12935-020-01702-0
|View full text |Cite
|
Sign up to set email alerts
|

Circ_ZFR contributes to the paclitaxel resistance and progression of non-small cell lung cancer by upregulating KPNA4 through sponging miR-195-5p

Abstract: Background A growing body of evidence has demonstrated the vital roles of circular RNAs (circRNAs) in cancer progression and drug resistance. We intended to explore the roles and mechanisms of circ_ZFR in the paclitaxel (PTX) resistance and progression of non-small cell lung cancer (NSCLC). Methods Two NSCLC cell lines A549 and H460 were used in this study. Quantitative real-time polymerase chain reaction (qRT-PCR) assay was conducted to measure th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 32 publications
0
38
0
Order By: Relevance
“…Circ_BIRC6 overexpression relieved PTX-induced repression of hepatocellular carcinoma progression through trapping miR-877-5p [ 29 ]. Additionally, circ_ZFR promoted PTX resistance in lung cancer in a miR-195-5p-dependent manner [ 30 ]. Circ_0061140 has been identified as a tumor promoter in bladder cancer [ 31 ], endometrial carcinoma [ 32 ] and prostate cancer [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Circ_BIRC6 overexpression relieved PTX-induced repression of hepatocellular carcinoma progression through trapping miR-877-5p [ 29 ]. Additionally, circ_ZFR promoted PTX resistance in lung cancer in a miR-195-5p-dependent manner [ 30 ]. Circ_0061140 has been identified as a tumor promoter in bladder cancer [ 31 ], endometrial carcinoma [ 32 ] and prostate cancer [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…An increasing amount of evidence has shown that circRNAs are involved in several physiological and pathological processes of tumor development and progression ( Song and Fu, 2019 ; Wang et al, 2019 ; Zhang et al, 2019a , b , c ; Bai et al, 2020 ; Zhang N. et al, 2020 ; Zhang S. J. et al, 2020 ). CircRNAs have also been shown to be involved in resistance to immunotherapy, targeted therapy, and chemotherapy ( Zhang et al, 2019b ; Wen et al, 2020 ; Li et al, 2021 ). In this study, we identified abnormal gene expression in LUAD with data from the GEO database.…”
Section: Discussionmentioning
confidence: 99%
“… 82 circ_ZFR up miR-195-5p 64 NSCLC tissue samples; A549 and H460 NSCLC cell lines silencing circ_ZFR inhibits PTX resistance, cell-cycle process, proliferation, migration, and invasion and promotes apoptosis in PTX-resistant NSCLC cells by sponging miR-195-5p to upregulate KPNA4 expression Li et al. 83 circGFRA1 up miR-188-3p 30 NSCLC tissue samples; A549 and H803 NSCLC cell lines upregulation of circGFRA1 promotes cancer cell proliferation by sponging miR-188-3p to activate the PI3K/AKT signaling pathway Yao et al. 84 hsa_circ_0014130 up miR-136-5p 30 NSCLC tissue samples; A549 and PC-9 NSCLC cell lines downregulation of hsa_circ_0014130 suppresses NSCLC progression by sponging miR-136-5p to increase Bcl-2 expression Geng et al.…”
Section: Overview Of Circrnasmentioning
confidence: 99%
“…The knockdown of circ_ZFR inhibits the taxol resistance of NSCLC by sponging miR-195-5p to decrease KPNA4 expression. 83 Some circRNAs, such as circ_0007385 and circ-PRMT5, are reported to be involved in the regulation of the DDP resistance of NSCLC cells. circ_0007385 knockdown has been shown to repress the DDP resistance of NSCLC cells.…”
Section: Overview Of Circrnasmentioning
confidence: 99%